A triangle study of human, instrument and bioelectronic nose for non-destructive sensing of seafood freshness - Lee, Kyung Mi (Sci Rep, 2018)
Because the freshness of seafood determines its consumer preference and food safety, the rapid monitoring of seafood deterioration is considered essential. However, the conventional analysis of seafood deterioration using chromatography instruments and bacterial colony counting depends on time-consuming and food-destructive treatments. In this study, we demonstrate a non-destructive and rapid food freshness monitoring system by a triangular study of sensory evaluation, gas chromatography-mass spectroscopy (GC-MS), and a bioelectronic nose. The sensory evaluation indicated that the acceptability and flavor deteriorated gradually during post-harvest storage (4 °C) for 6 days. The GC-MS analysis recognized the reduction of freshness by detecting a generation of dimethyl sulfide (DMS) from the headspace of oyster in a refrigerator (4 °C) at 4 days post-harvest. However, the bioelectronic nose incorporating human olfactory receptor peptides with the carbon nanotube field-effect transistor sensed trimethylamine (TMA) from the oyster at 2 days post-harvest with suggesting early recognition of oysters’ quality and freshness deterioration. Given that the bacterial species producing DMS or TMA along with toxins were found in the oyster, the bacterial contamination-driven food deterioration is rapidly monitored using the bioelectronic nose with a targeted non-destructive freshness marker.